Pengaruh Motivasi Kerja dan Komitmen Kerja terhadap Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kota Jambi - Amelia Putri; Sumarni Sumarni; Nur Hasanah (Politeknik Kampar, 2024)
This research aims to see the influence of work motivation and work commitment on employee performance at the Dinas Kependudukan dan Pencatatan Sipil Kota Jambi service using data collection techniques by distributing questionnaires to 88 respondents. Hypothesis testing uses Descriptive Analysis Techniques the SPSS application as a data processing tool. The results of this research show that work motivation has a positive and significant influence on the Dinas Kependudukan dan Pencatatan Sipil Kota Jambi. work commitment has a positive and significant influence on employee performance. Sugestions in the research: 1) regarding employee permomance variables, employees should make better work planning so that employees can complete work on time. 2) in the work motivation variabels, superiors should be better able to organize and survise employees so that employees have motivation from superiors so that employee performance can be even better. 3) in work commitment variable, employee should have a greater sense of family towards the angency/organization because the organization’s agency has a lot of meaning for each employee.